Dual Photoredox/Palladium-Catalyzed C–H Acylation of 2-Arylpyridines with Oxime Esters - He, Bin-Qing; Gao, Yuan; Wang, Peng-Zi; Wu, Hong; Zhou, Hong-Bin; Liu, Xiao-Peng; Chen, Jia-Rong (Synlett, 2021)
An unprecedented dual photoredox/palladium-catalyzed iminyl-radical-mediated C–C bond cleavage and directed ortho C–H acylation of 2-arylpyridines by using oxime esters is described. Oxime esters can serve as efficient acyl sources through formation of the corresponding acyl radicals by photoredox-catalyzed iminyl-radical-mediated C–C bond cleavage. This redox-neutral protocol features excellent regioselectivity, a broad substrate scope, and good functional-group tolerance with respect to both components, giving a broad range of aryl ketones with generally good yields.
Keywords: photocatalysis; palladium catalysis; C–H activation; acylation; iminyl radical; oxime esters